SABER Country Report –Senegal: Engaging the Private Sector in Education - World Bank (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:LIJPA522

Community Development through Open Learning and Distance Education - Mehmood, Tahir; Hussain Ch, Abid; Saeed, Amna (Bulletin of Education and Research, 2016)
The global need for community development is greater now in the early 21st century than ever before. According to UNESCO, half of the world's 195 countries will have to expand their stock of educationist significantly, some by tens of thousands, if the goal development targets are desired to achieve. Socioeconomic inequities, political instability, demographic changes and crises such as the HIV/AIDs epidemic have engendered huge shortfalls in teacher supply and low teacher quality in many developing countries. Education serves as back bone in development process. Open learning and distance education programs are serving as pivotal part of development process. It is now clear that "bricks and mortar" approaches to expanding teacher education may not be adequate if the current and projected shortfalls in teacher supply and low teacher quality are to be properly addressed. The study is designed to measure the perceptions of teaching learning community about community development with special reference to open and distance learning. It was descriptive study which targeted teachers, students, community members and experts. Data analysis was carried out by using statistical techniques served by SPSS. Findings reflected that audience perceives open and distance learning as change agent and as development tool. It is noticed that target audience has driven prominent performance by using facility of open and distance learning.
Publisher: Institute of Education and Research KerkoCite.ItemAlsoKnownAs: 2339240:VXX3G7KQ 2405685:GTVRNDQ9
Keywords: Access to Education; Change Agents; Community Development; Developing Nations; Distance Education; Economic Development; Educational Change; Educational Quality; Foreign Countries; Gender Differences; Nongovernmental Organizations; Open Educational Resources; Social Differences; Specialists; Student Attitudes; Teacher Attitudes; Teacher Shortage; ⛔ No DOI found

Digital Learning Programme - Ministry of Education, Kenya (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:IP7DIJBT

Tusome Early Grade Reading Activity - RTI International (RTI, 2016)
Across Kenya, literacy rates in primary schools are significantly lower than expected despite increased access and enrollment. The Kenyan education system is seeking to improve learning outcomes by instilling better instructional practices, expanding resources for teacher training, and developing learning materials that support multilingual literacy. Kenya’s approach to the challenge of raising literacy and learning outcomes is unique in its ambitious goals and well-researched methods for achieving its goal at a national scale.
Library Catalog: www.rti.org KerkoCite.ItemAlsoKnownAs: 2339240:XNM3FD3A 2405685:GEG6RSZ3 2405685:NNFW4F3L GEG6RSZ3

Home - Ministry of Education, Kenya (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:PKXCNKUD

Social Media Integration in Secondary Education in Pakistan - Ahmed, Rida (Journal of Education and Educational Development, 2016)
This paper investigates the adequacy of social media implementation in the context of secondary education in Pakistan and highlights the importance and necessity of social media in secondary education. This research has helped in understanding the pros and cons of social media implementation in classrooms and also facilitated in analyzing whether social media helps in student learning, classroom performances, competencies and academic grow. The qualitative study paradigm was used for this research. Six phenomenological interviews were conducted from secondary school teachers. In the light of the derived results. It was concluded that social media was an essential tool that could be used to make classrooms more engaging and ethnically diverse. Results suggested that teachers spent time implementing social media in their classrooms for academic purposes and teachers used these forums for self-education and to interact with like-minded people. Social media can serve the most momentous purposes in education system as today's digitalized world is all about the Internet and technology, and hence it becomes compulsory for the educationist to understand the importance social networking
Publisher: Institute of Business Management, Department of Education KerkoCite.ItemAlsoKnownAs: 10.22555/joeed.v3i1.712 2339240:4BTHKM5D 2405685:F6SK6AJK
Keywords: Classroom Techniques; Educational Resources; Educational Technology; Foreign Countries; Guidelines; Information Policy; Interviews; Phenomenology; Program Implementation; Qualitative Research; Relevance (Education); Secondary School Teachers; Social Media; Teacher Attitudes; Technology Integration; Technology Uses in Education

Harnessing the Potential of ICTs: Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets and Computers - Hanemann, Ulrike; Scarpino, Cassandra (UNESCO Institute for Lifelong Learning, 2016)
The UNESCO Institute for Lifelong Learning (UIL) has published a second edition of "Harnessing the Potential of ICTs: Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets and Computers." This compilation of case studies from all world regions presents promising literacy and numeracy programmes that use information and communication technologies (ICTs) in their access and outreach strategies. The twenty-six case studies illustrate how ICTs such as radio, TV, mobile phones, tablets and computers can be used as media of instruction, can supplement face-to-face teaching, and can help to develop and strengthen youth and adult literacy, language and numeracy skills. The case studies featured in this publication can also be found in the UNESCO Effective Literacy and Numeracy Practices Database (LitBase). [For the 1st Edition: "Harnessing the Potential of ICTs for Literacy Teaching and Learning: Effective Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets, and Computers," see ED560504.]
KerkoCite.ItemAlsoKnownAs: 2339240:EHGHB4P6 2339240:JK88DX53 2405685:24SDVCB2 2405685:WAVX3A5A
Keywords: Adult Literacy; Case Studies; Distance Education; Educational Technology; Foreign Countries; Handheld Devices; Instructional Materials; Literacy Education; Mathematics Education; Numeracy; Program Content; Program Effectiveness; Radio; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; Television; Videoconferencing

Pakistan’s Education Crisis: The Real Story - Naviwala, Nadia (Wilson Center, 2016)
KerkoCite.ItemAlsoKnownAs: 2339240:B783KRE8 2339240:VDL9MRA7 2405685:APRFWT5B 2405685:JMXYPLHM 2405685:LBVR8VFV
Keywords: Advantaged; Armed Forces; Attendance; Budgets; Educational Change; Educational Finance; Educational Policy; Educational Quality; Expenditures; Foreign Countries; International Organizations; Interviews; Political Influences; Privatization; Specialists; Standards; Teacher Attendance; Teacher Salaries

The Effect of Teachers' Professional Development in Video Technology on Mathematics and the English Language Learning of Preschoolers in a Rural Primary School in Pakistan. - Ikram, Hamid (2016)
The purpose of this mixed methods study was to examine the effect of teachers' professional development in video technology (PBS & Sesame Street videos) on mathematics and the English language learning among nursery students in the rural area of Pakistan where it was impossible for students to experience watching videos for learning purposes. This study showed teachers' motivation and frustration, before and after professional development, toward the use of video technology in the classroom. Also, this study showed the effect of learning videos assisted with games, coloring activities, and portfolios on student's English and mathematics' learning. The demographics of gender, socioeconomic status of the students, parents' education and occupation, learning resources at home for children, and the use of technology and media at home were contrasted to examine how they affect students learning of mathematics and English. The participants of the study were 80 nursery students and two English and math teachers in a rural primary school of Punjab province in Pakistan. Data were collected through a semi-structured interview protocol, biographical survey, and English and math tests. The demographic characteristics of the participants revealed that there were 55 percent female students and 45 percent male students ranging in age from 4 to 6 years. The demographics also revealed that 81 percent of the students belonged to households that had not more than $100 income per month. The findings supported that a majority of the students belonged to low socioeconomic status (SES), and fathers were the main source of household income. The findings showed that fathers' level of education was higher than that of the mothers' level of education. The effective delivery of the content with videos and students' engagement motivated teachers. The use of videos remarkably enhanced students' learning of math numbers and English alphabet in experimental classrooms. However, the lack of funds and technology training was the biggest frustration for teachers. The findings from this research contributed to the literature about teachers' professional development and use of learning media. The findings also identified the reasons behind teachers' frustration and motivation to bring technology in the classroom. Consequently, these study findings informed administrators, teachers, and parents to improve existing teaching and learning practices at early education level in Pakistan. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
KerkoCite.ItemAlsoKnownAs: 2339240:FLFX5IGI 2339240:GEMLTXYF 2405685:KFYBLHY6 2405685:RP6L4XQU
Keywords: Educational Media; Educational Technology; Elementary School Teachers; English Language Learners; Foreign Countries; Mathematics Education; Mathematics Instruction; Mixed Methods Research; Pakistan; Preschool Children; Professional Development; Rural Schools; Second Language Learning; Semi Structured Interviews; Surveys; Technology Uses in Education; Video Technology